High genetic diversity and superinfection by Anaplasma marginale strains in naturally infected Angus beef cattle during a clinical anaplasmosis outbreak in southeastern Brazil - Garcia, Amanda Barbosa [UNESP]; Jusi, Márcia Mariza Gomes [UNESP]; Freschi, Carla Roberta [UNESP]; Ramos, Inalda Angélica Souza [UNESP]; Mendes, Natália Serra [UNESP]; Bressianini do Amaral, Renan [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (Elsevier, 2022)
Anaplasma marginale is an obligate intracellular Gram-negative bacterium that is parasitic to erythrocytes and is the main agent of bovine anaplasmosis. This disease causes severe anemia and reduces weight gain and milk production, thus giving rise to major economic losses relating to livestock worldwide. The genetic diversity of this bacterium has been characterized based on sequences of major surface proteins (MSPs), especially MSP1α. This has enabled identification of several geographical strains, according to different amino acid sequences. The aim of this study was to investigate the genetic diversity of A. marginale in naturally infected Angus beef cattle during a disease outbreak in southeastern Brazil. Four blood samples were collected over a four-month period from each of 20 animals on a cattle farm in Itú, São Paulo, Brazil. Serum samples were subjected to indirect ELISA to detect anti-A. marginale IgG antibodies. The 80 whole-blood samples obtained were subjected to DNA extraction, quantitative real-time PCR (qPCR) for the msp1β gene, semi-nested PCR (snPCR) for the msp1α gene, cloning of the target fragment and sequencing using the Sanger method. The sequences obtained were analyzed for genetic diversity using the RepeatAnalyzer software. Both iELISA tests, using recombinant MSP5 and the Anaplasma antibody test kit (VMRD), revealed high seroprevalence: 91.25% and 97.5%, respectively. In qPCR, 100% of the samples were positive, with between 103 and 107 DNA copies/μL. In the snPCR based on the msp1α gene, 57.5% (46/80) of the samples were positive. Microsatellite analysis on the 36 sequences obtained showed the presence of genotypes H (58.3%), F (25%), E (19.4%), C (2.7%) and G (2.7%). The RepeatAnalyzer software identified 36 strains in the study region, among which some had not previously been described in the literature (13 27 13 27 13 F; 16 FF; τ 27; 63 29 104 29; LJ1 13 LJ1 13; 16 F 17; 16 F 91). High genetic diversity of A. marginale bacteria was found on this farm in Itú, São Paulo.
Keywords: Bovine anaplasmosis; Genotype; Msp1α; Tandem repeats